Review article: Evacuating hospitals in Australia: What lessons can we learn from the world literature?. (13th November 2013) - Rojek, Amanda; Little, Mark
Abstract The creation of hospitals safe from disaster is an area of increasing public policy. The vulnerability of hospitals to damage and destruction during an event has profound implications for the health of a community. Although hospital evacuations do occur in Australia, their prevalence is unknown and what leads to a successful evacuation is poorly understood. This article reviewed the worldwide hospital evacuation literature to determine the prevalence of hospital evacuations and common precipitants for evacuation. Factors leading to safe evacuation and areas of ongoing challenge were identified. The findings highlight the need for more structured and detailed reporting of hospital responses to disaster. A number of lessons can be learned from hospitals that have experienced evacuation. Most critically, all hospitals must have a practised, detailed hospital evacuation plan existing before an impending threat. There are also areas for improvement in the areas of assessing the risk to the facility, communications, leadership, logistics, staffing and planning. These lessons should be included into comprehensive, detailed evacuation plans for all Australian hospitals, supported by a national framework that standardises planning and response.